2013
DOI: 10.1002/ajmg.a.35779
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of ZNF238 is associated with corpus callosum abnormalities in 1q44 deletions

Abstract: A variety of candidate genes have been proposed to cause corpus callosum abnormalities (CCAs) in patients with terminal chromosome 1q deletions. Recent data excluded AKT3 and implicated ZNF238 and/or CEP170 as genes causative of corpus callosum anomalies in patients with 1q43-1q44 deletions. We report on a girl with dysmorphic features, seizures beginning in infancy, hypotonia, marked developmental delay, and dysgenesis of the corpus callosum. Chromosomal microarray analysis detected a de novo 1.47 Mb deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
1
20
2
1
Order By: Relevance
“…The majority (66%) developed seizures. 1, [8][9][10][11][12]15 Incomplete penetrance is a possible explanation for the absence of ACC in this girl, given that the corpus callosum was apparently normal in at least five patients with 1q43q44 microdeletions that included ZBTB18 as described previously. 1,9,12 We note that brainspecific loss of ZBTB18 in mice leads to a small brain phenotype with ACC and cerebellar hypoplasia.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The majority (66%) developed seizures. 1, [8][9][10][11][12]15 Incomplete penetrance is a possible explanation for the absence of ACC in this girl, given that the corpus callosum was apparently normal in at least five patients with 1q43q44 microdeletions that included ZBTB18 as described previously. 1,9,12 We note that brainspecific loss of ZBTB18 in mice leads to a small brain phenotype with ACC and cerebellar hypoplasia.…”
Section: Discussionsupporting
confidence: 58%
“…1, 3,[8][9][10][11][12][13][14] Specifically, ZBTB18 has repeatedly been identified as a strong candidate gene for microcephaly and/or ACC. 7,9,11,14,15 ZBTB18 is particularly compelling since a brain-specific knock-out of this gene in mice causes microcephaly and callosal anomalies. 16 However, other studies suggest critical regions that do not include ZBTB18.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to 1q43-44 deletion -out of 41 cases where inheritance was documented, only six were inherited (14.63%) [Boland et al, 2007;Hill et al, 2007;Poot et al, 2008;van Bon et al, 2008;Orellana et al, 2009;Caliebe et al, 2010;Ballif et al, 2012;Perlman et al, 2013]. This suggests that the impact of pure AKT3 deletions on reproductive fitness is much less than that of the larger 1q43-44 deletions.…”
Section: Discussioncontrasting
confidence: 71%
“…Previous studies have reported that 1q43-q44 CNVs are associated with intellectual disability (also referred to as mental retardation), microcephaly and corpus callosum abnormalities [Boland et al, 2007;van Bon et al, 2008;Caliebe et al, 2010;Nagamani et al, 2012;Perlman et al, 2013]. Given such neurological impairments in our patient (Fig.…”
Section: Q43-q44 Cnvs Are Associated With Neurological Impairmentmentioning
confidence: 64%